The Role of Periostin in Breast Cancer - Zainab Ali Ghazi Lazim; Ghada Jamal Jasem Mohamed; Abeer nawzat ahmed shareef; Ghufran Iyad Fares Saleh; Sahar mohammed taih kreedy (Genius Journals, 2024)
Periostin (POSTN), a member of the matricellular protein family, is a secreted adhesionrelated protein produced in the periosteum and periodontal ligaments. Matricellular proteins are a nonstructural family of extracellular matrix (ECM) proteins that regulate a wide range of biological processes in both normal and pathological conditions. The studies have demonstrated the key roles of these ECM proteins in the tumor microenvironment. Furthermore, periostin is an essential regulator of bone and tooth formation and maintenance, as well as cardiac development. Also, periostin interacts with multiple cell-surface receptors, especially integrins, and triggers signals that promote tumor growth. According to recent studies, these signals are implicated in cancer cell survival, epithelial-mesenchymal transition (EMT), invasion, and metastasis. In this project, we will summarize the most current data regarding periostin, its structure and isoforms, expressions, functions, and regulation in cancerous tissues, and emphasis will also be placed on its association with breast cancer
Keywords: Breast Cancer; Periostin; matricellular protein